Efficiency in the provision of social care for older people. A three-stage Data Envelopment Analysis using self-reported quality of life. (March 2015) - Iparraguirre, José Luis; Ma, Ruosi
Abstract: Using a three-stage data envelopment analysis approach, this paper explores efficiency in the provision of social care for older people in 148 English Councils in 2009/10. Departing from D'Amico and Fernández (2012) [31] our measure of efficiency is inscribed within the production of welfare framework and based on self-reported quality of life of recipients of the services. Our results indicate a high level of efficiency, but once we control for the effects of a number of environmental variables, we found that more stringent eligibility criteria and higher assessment costs are negatively associated with the efficiency in the provision of social services. Highlights: Three-stage DEA model to analyse efficiency in the provision of social care to older people. Benchmark efficiency based on quality of life within production of welfare approach. More stringent eligibility associated with lower quality of life.